Comparative performance of Poplar, Melia and Eucalyptus based agroforestry systems - Dhiman, R.C.; Gandhi, J.N. (Indian Journal of Agroforestry, 2020)
The present study compares the performance of three agroforestry systems viz. melia based agroforestry (MBAF), poplar based agroforestry (PBAF) and eucalyptus based agroforestry (EBAF) among each other and with open conditions growing similar intercrops under similar conditions in the Tarai region of Uttar Pradesh. Intercrops grown in the experimental field were sugarcane during first year, ratoon sugarcane during second year, wheat crop during second winter season, oat as fodder crop during third winter season and dhaincha as green manure during fourth summer season. At 56 months of age, melia trees have grown more in DBH and crown diameter than eucalyptus and poplar trees, though their height was significantly less than the trees of other two species. There was more reduction in intercrop yields under the canopy of melia (40.51%) than that of poplar (25.65%) and eucalyptus (21.05%) trees. At five years age, PBAF produced higher net returns of Rs. 358330 ha-1 compared to Rs. 322462 ha-1 from EBAF, Rs. 214621 ha-1 from MBAF and Rs. 277567 ha-1from growing the same crops under open conditions. Returns from EBAF could have been less if the generally followed practice of dense planting over 1250 trees ha-1 was followed compared to just 500 considered in this trial to keep the uniformity in tree density and intercrops.